Apresentação de dossiê - Luzia Alzira Zuin, Aparecida Luzia Alzira Zuin; Fernando Barcellos Xavier, Delson; Motta, Maurício; Bernardes Maganhini, Thaís (REVISTA QUAESTIO IURIS, 2024)
Apresentação do dossiê de Rondonia 2023